REEMISJA W ŚWIETLE ZMIAN PRAWA AUTORSKIEGO - Błeszyński, Jan (Zeszyty Prawnicze, 2017)
REEMISSION IN THE LIGHT OF CHANGES IN THE COPYRIGHT LAW Summary An author’s output, artistic performances, rights to phonograms and videograms, rights to radio and television broadcast, constitute an essential element of the media market. The audiences respond and in the result prospects for advantages depend on the attractiveness of the authors’ and their artistic input. It is obvious, that the broadcasters’ dream is that the program is both: attractive to the audience and cheap. Broadcasters’ economic domination results in the possibility to force lower remuneration paid to authors and artists. This domination, however, is only an illusion, because the worse economic conditions for artists and authors are, the lower quality of programs we can get. It is impossible to expect an author or artist to accept unprofitable conditions. The amendments to the Copyright Act with regard to radio-television rights were introduced in 1998 in order to adapt Polish copyright for EU requirements. At this opportunity, several other changes were introduced, which were not conditioned by those requirements, and sometimes were even contradictory to them! The promoter of the amendment to the Copyright Act introduced in 1998 and 1999 was Andrzej Zakrzewski - the Minister of Culture and National Heritage at that time. It was meant to be a continuation of the changes introduced in 1994. A great number of provisions adopted in 1994 did not provide for the protection standards required by the EU laws, which was due to the necessity to make the consequences of the adaptation „softer”. An example is the amendment to radio-television rights. The drafts of of the amendments prepared in 1998 introduced cancellation of the statutory license to a reemission and replacing it by agreements concluded with organizations of collective management. Issues related to broadcasts and reemission were placed in Article 21, which resulted in the repeal of Article 23 Section 4 of the Copyright Act of 1994. Contrary to the above draft, in a report presented to the Commission of Culture and Mass Media, the repeal of Article 24 Section 3 as well as the definition of a „reemission” were decided to be crossed out. In the course of debates on the amendments, Senate voted for replacing the phrase „reemission” with the term „parallel and integral dissemination” and repealing Art. 24 Section 3. The amendment of 9 June 2000 upheld Art. 24 Section 3, which was a technical mistake resulting from internal discrepancies within the act of law introducing the amendments. The amendment of 28 October 2002 removed this provision. The proposal to repeal Art. 24 Section 3 was accompanied with a proposal to add to Article 2 1 a new section no. 4 stating, that: „in case of any discrepancies resulting from the agreement, referred to in Section 3, Article 108 Section 5 shall apply”. The reason for such an amendment was to soften the consequences of removing the statutory license with regard to a reemission in 2000. Article 108 Section 3 of the Copyright Act of 1994 in its first version, with regard to the discrepancies resulting from Remuneration Schedules approved of by the Copyright Commission consisting of 7 members, provided for a jurisdiction of the Copyright Commission consisting of 3 members. The Copyright Commission consisting of 3 members, deciding on „discrepancies resulting from the agreement on reemission”, threatens the authors’ rights. It is necessary to indicate, that an author is vested with an exclusive right to dispose of his work. In a situation where there is a statutory license, an author is only vested with a right to remuneration. In any situation, however, an organization of the collective management acts for his benefit. Extending the scope of the Copyright Commission’s jurisdiction cannot lead to limiting the authors’ rights. An extended jurisdiction of the Copyright Commission in fact creates such a limitation. Instead of negotiating a license to a reemission, including an author’s remuneration, apart from the collective management body, a cable operator may obtain a license for a reemission issued by the Copyright Commission consisting of 3 members. After the aforementioned amendment came into force, the issue of a statutory license with regard to cable television became a subject of intensive media discussion. Just a few months after the amendment was introduced, the deputies proposed to go back to the statutory license with regard to a reemission. As a result, a new amendment was adopted, which reintroduced the statutory license. The aforementioned changes, however, were made being aware of their contradiction to the EU standards. Opponents of these changes raised arguments speaking for the necessity of further amendments. Some of them are as follows. A cable operator was to have just a few days to identify television programs’ broadcasters, start negotiations, and conclude appropriate agreements. This argument took no account of the fact, that a removal of the statutory license with regard to reemission was made in 2000. As a result, the introduced amendment repeals Article 21 Section 3 and 4 of the Copyright Act of 2002 and replaced it with a new Article 211 which shall come into force on the date when Poland joins the European Union. It means, that in place of temporarily removed provisions abolishing the statutory license, it has been brought into the light again, due to the European Union obligations. The changes adopted in 2002 were appealed, however, because of being contradictory to the Polish Constitution - too short vacatio legis. Constitutional Tribunal in its decision of 16 September 2003 did not agree with this view. It means, that Constitutional Tribunal did not share the argument which justified bringing the statutory license in 2003 into the light again.